An unusual presentation of chondroid syringoma - Dilip Chandra Barman; Abhijit Bhowmik (Wolters Kluwer Medknow Publications, 2016)
Chondroid syringoma (CS) is a rare benign tumor of the sweat gland. It generally presents as a painless, slowly growing, subcutaneous swelling, typically located on the head and neck region. The majority of the cases develop in middle aged and elderly males. We present a case of CS located over the right thumb of a 25-year-old male. The diagnosis was made initially by cytological evaluation and later confirmed by histopathological examination. There was no recurrence on two year follow up after the complete surgical excision of the tumor.